Tone management of voluntary disclosures in Brazilian public companies’ press releases - Souza, Paulo Vitor Souza de; Silva, Polyana Batista da (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This study seeks to verify whether Brazilian public companies manipulate qualitative information through tone management. Forty-three companies were selected from Brazil's Ibovespa, Bolsa e Balcão (B3), with quarterly data from 2017 to 2018. The data regarding positive tonality were formatted using Loughran and McDonald (2011) word classification, taken from press releases voluntarily released by the companies and analyzed by the software Atlas.ti8. The index was regressed against the discretionary accruals obtained in two results management models. The results point to a negative and significant relationship between accounting management and positive tone of reporting, i.e. companies with higher positive tone manage less results. These findings present relevant information as they highlight the quality of the texts contained in the companies' reports.